2014
DOI: 10.1371/journal.pone.0086722
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Hippocampal GABAA/cBZR Density with [18F]-Flumazenil PET for the Study of Disease Progression in an Animal Model of Temporal Lobe Epilepsy

Abstract: PurposeImbalance of inhibitory GABAergic neurotransmission has been proposed to play a role in the pathogenesis of temporal lobe epilepsy (TLE). This study aimed to investigate whether [18F]-flumazenil ([18F]-FMZ) PET could be used to non-invasively characterise GABAA/central benzodiazepine receptor (GABAA/cBZR) density and affinity in vivo in the post-kainic acid status epilepticus (SE) model of TLE.MethodsDynamic [18F]-FMZ -PET scans using a multi-injection protocol were acquired in four male wistar rats for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Investigational tracers bind to neuroreceptors as gamma-aminobutyric acid (GABA) receptor, serotonin receptors or targets associated with neuroinflammation, 6,7 as the imbalance between glutamatergic and gabaergic neurotransmission as well as neuroinflammation are considered to play a key role in epileptogenesis. 14 In addition, imaging studies have shown down-regulation of GABA A receptors after the epileptogenic insult [15][16][17] and decrease of metabotropic glutamate receptor 5 (mGluR5) in the acute and subacute phases after SE recovering baseline levels in the chronic phase. Thus, animal models are used to study alterations during epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Investigational tracers bind to neuroreceptors as gamma-aminobutyric acid (GABA) receptor, serotonin receptors or targets associated with neuroinflammation, 6,7 as the imbalance between glutamatergic and gabaergic neurotransmission as well as neuroinflammation are considered to play a key role in epileptogenesis. 14 In addition, imaging studies have shown down-regulation of GABA A receptors after the epileptogenic insult [15][16][17] and decrease of metabotropic glutamate receptor 5 (mGluR5) in the acute and subacute phases after SE recovering baseline levels in the chronic phase. Thus, animal models are used to study alterations during epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…injection of the glutamate receptor agonist, KA, to induce a period of continuous seizure activity (status epilepticus) in non-epileptic rats as described previously (Hellier et al, 1998;Powell et al, 2008;Jupp et al, 2012;Powell et al, 2014b;Vivash et al, 2014).…”
Section: Ka-induced Post-se Rat Modelmentioning
confidence: 99%
“…17 In Rhesus monkeys, socially dominant females were shown to have lower GABA receptor density in the prefrontal cortex than socially submissive animals by PET studies using [ 18 F]flumazenil, but administration of the corticotropin-releasing hormone astressin B to submissive females eliminated this effect. 16 [ 11 C]Ro15-4513 and [ 3 H]Ro15-4513 were used in in vitro studies of rat brain tissue to investigate the effects of vigabatrin, tiagabine, and SNAP-5114 on receptor agonist distribution.…”
Section: γ-Aminobutyric Acid-benzodiazapine Receptormentioning
confidence: 99%